Research progress of self-assembling peptide hydrogels in repairing cartilage defects - Wang, Renyi; Wang, Yuhao; Yang, Han; Zhao, Chengzhi; Pan, Jian (Frontiers in Materials, 2022)
Due to the lack of blood vessels, nerves and lymphatic vessels, the capacity of articular cartilage to heal is extremely limited. Once damaged, it is urgent for articular cartilage to repair the injury. In recent years, there has been an increase in cartilage tissue engineering studies. Self-assembling peptide hydrogel (SAPH) as a kind of hydrogels composed of peptides and water is widely used in cartilage tissue engineering. Under noncovalent interactions such as electrostatic interactions, hydrophobic interactions, hydrogen bonding and pi-pi stacking force, peptides self-assemble into three-dimensional (3D) structures that mimic the natural extracellular matrix (ECM) and allow cells to grow, proliferate and differentiate. Because SAPHs have excellent biocompatibility and biodegradability, variable mechanical properties, low immunogenicity, injectability, and the ability to load cells and bioactive substances, many researchers utilized them to promote the repair and regeneration of articular cartilage after damage. Therefore, the purpose of this review is to sum up the composition, injury characteristics, and treatment of articular cartilages, as well as the action of SAPHs in repairing articular cartilage damage.